Managerial bonuses, subordinates' disobedience, and coercion - Nikos Nikiforakis; Jörg Oechssler; Anwar Shah (University of Heidelberg, Department of Economics, 2015)
This study provides evidence from a laboratory experiment showing that managerial bonuses can affect adversely a manager's subordinates. In our set up, managers compete to obtain a large bonus which depends partly on the effort exerted by their subordinates. Managers can suggest an effort level and coerce subordinates who disobey by punishing them. When managers compete for individual bonuses, we find that subordinates do not obey their demands. This doubles coercion rates relative to a control treatment without bonuses. In contrast, when managers compete for pooled bonuses which give managers discretionary power over the allocation of the bonus, most subordinates exert maximal effort. Although managers share a substantial fraction of the bonus, they are not worse off than they are with an individual bonus. A model in which agents care about inequality in earnings can account for the main findings in our experiment.
urn:nbn:de:bsz:16-heidok-185802
Keywords: 330; coercion; managerial incentives; disobedience; hierarchy; tournament